Imagining Sameness and Difference in Children's Literature
XIV, 268 p. 29 illus.
Keywords: This book investigates how cultural sameness and difference has been presented in a variety of forms and genres of children’s literature from Denmark, Germany, France, Russia, Britain, and the United States; ranging from English caricatures of the 1780s to dynamic representations of contemporary cosmopolitan childhood. The chapters address different models of presenting foreigners using examples from children’s educational prints, dramatic performances, travel narratives, comics, and picture books. Contributors illuminate the ways in which the texts negotiate the tensions between the Enlightenment ideal of internationalism and discrete national or ethnic identities cultivated since the Romantic era, providing examples of ethnocentric cultural perspectives and of cultural relativism, as well as instances where discussions of child reader agency indicate how they might participate eventually in a tolerant transnational community. .